Austempering in Zamak bath : influence of austempering time and austenitizing temperature on ductile cast iron properties - Pereira, Leonardo (2019)
The combination of the austempered ductile iron mechanical properties strongly depend on the parameters used on the austempering cycle. On this study, the influence of austempering time and austenitizing temperature on the properties of a ductile iron were evaluated. A metallic bath of Zamak at 380°C was used as an austempering mean. A set of ductile iron blocks were austenitized at 900°C for 90 minutes and submitted to different austempering times in order to determine the best combination of microstructural and mechanical properties. After the definition of the time of austempering, the reduction of the austenitizing temperature was evaluated. The best combination of properties was obtained with austenitizing at 860°C and austempering during 60 minutes.